Metode Tafsir Tematik Kontekstual Abdullah Saeed - Abd. Muqit (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The backwardness of Muslims at this time was caused by the freezing of Islamic scholarship. This happens because some people think that ijtihad has been closed. In this contemporary century, some Muslim academics are trying to revive Islamic scholarship, both from the aspect of methodology and theoretical products. One of the Islamic thinkers who is trying to develop a new methodology is Abdullah Saeed, a professor of Arabic and Islamic Studies who is active at the University of Melbourne, Australia. This research tries to explore Abdullah Saeed's thoughts in the field of contextual thematic interpretation methods. The research results are as follows: First, the contextual thematic interpretation method is an interpretation method that must consider three principles, namely 1). Pay attention to and consider various meanings, then take the relevant meaning; 2). Pay attention to and consider the socio-historical context of the revelation of the Koran to determine the food that the mufassir will take; 3). Pay attention and consider the hierarchical value of the Koran to find out which verses can be re-interpreted (dhanni) and which cannot be re-interpreted (qath'i). Second, how the contextual thematic interpretation method works is as follows: 1). Determine the theme; 2). Determine the hierarchical value of the verse text; 3). Exploring the Macro and Micro Context of the Seventh Century; 4). Analyzing Linguistics; 5). Collecting Parallel Texts of the Koran; 6). Present contextualization.